2022
DOI: 10.1186/s12879-022-07486-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaccine hesitancy on secondary COVID-19 outbreaks in the US: an age-structured SIR model

Abstract: Background The COVID-19 outbreak has become the worst pandemic in at least a century. To fight this disease, a global effort led to the development of several vaccines at an unprecedented rate. There have been, however, several logistic issues with its deployment, from their production and transport, to the hesitancy of the population to be vaccinated. For different reasons, an important amount of individuals is reluctant to get the vaccine, something that hinders our ability to control and—eve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…As COVID-19 spread around the globe and the number of active infections and death tolls increased, the need for a vaccine to fight the pandemic became increasingly more critical. However, the rapidity of vaccine development and approval and concerns regarding the vaccine’s safety, effectiveness and side effects have contributed to a lack of vaccine confidence and lower vaccination uptake rates in the general population [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As COVID-19 spread around the globe and the number of active infections and death tolls increased, the need for a vaccine to fight the pandemic became increasingly more critical. However, the rapidity of vaccine development and approval and concerns regarding the vaccine’s safety, effectiveness and side effects have contributed to a lack of vaccine confidence and lower vaccination uptake rates in the general population [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine hesitancy has a wide range of negative consequences, from the more obvious health effects on unvaccinated individuals who become infected, to the more subtle, but likely larger, consequences for increased infection rates, especially within the social circles of unvaccinated individuals. For example, de Miguel-Aribas and colleagues [ 8 ] modeled the effect of COVID-19 vaccine hesitancy in the US and found that for each one percent decrease in vaccine hesitancy, the primary and secondary effects resulted in an aggregate of 45 deaths per million inhabitants averted.…”
Section: Introductionmentioning
confidence: 99%
“…Mass vaccination represents a crucial strategy in preventing and mitigating the spread of infectious diseases through the establishment of herd immunity [1], protecting even unvaccinated individuals. Despite its demonstrated benefits, vaccine hesitancy remains a persistent issue, compounded by challenges posed by the ongoing COVID-19 pandemic [2, 3,4,5,6,7]. Heightened concerns regarding vaccine safety and efficacy have exacerbated the long-standing challenge of voluntary vaccination [8,9,10].…”
Section: Introductionmentioning
confidence: 99%